2016
DOI: 10.24953/turkjped.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin resistance and 23S rRNA gene point mutations of Helicobacter pylori infection in children

Abstract: This study aims to evaluate Helicobacter pylori with clarithromycin resistant genotypes in Manisa region, Turkey. Two hundred patients, who received diagnosis of Helicobacter pylori infection histopathologically, were included. The sex, age and endoscopy indications of the patients were recorded. Polymerase chain reaction method was applied to determine the clarithromycin resistance rate and resistance genotypes at the histologic sections prepared from gastric biopsies that had been embedded in paraffin after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…23 H. pylori strains were found to carry A2143G, A2142G, A2147G and A2146G mutations that can lead to clarithromycin-resistance in Africa, Asia, South America, Europe and North America. [24][25][26][27][28][29][30] The T2183C and A2223G transformations have been frequently found to be the cause of observed clarithromycin resistance in Asian countries than those in Europe and North America, 31 but not be observed in our study. In addition to these mutations, other mutations in different positions have been found in other parts of the world to confer clarithromycin resistance in H. pylori strains (T2182C, T2190C, C2195T, A2223G, G2141A, C2694A, G2224A, C2245T, T2289C).…”
Section: Discussioncontrasting
confidence: 62%
“…23 H. pylori strains were found to carry A2143G, A2142G, A2147G and A2146G mutations that can lead to clarithromycin-resistance in Africa, Asia, South America, Europe and North America. [24][25][26][27][28][29][30] The T2183C and A2223G transformations have been frequently found to be the cause of observed clarithromycin resistance in Asian countries than those in Europe and North America, 31 but not be observed in our study. In addition to these mutations, other mutations in different positions have been found in other parts of the world to confer clarithromycin resistance in H. pylori strains (T2182C, T2190C, C2195T, A2223G, G2141A, C2694A, G2224A, C2245T, T2289C).…”
Section: Discussioncontrasting
confidence: 62%
“…In another Turkish study, Çagan-Appak et al [ 36 ] reported resistance to clarithromycin in gastric biopsies of 19/200 (9.5%) children with dyspepsia and abdominal pain; 10/19 (52.6%) had A2143G mutations, and 9/19 (47.4%) had A2142G mutations. There were no A2142C mutations.…”
Section: Discussionmentioning
confidence: 99%